Distinct Effects of Platelet-Rich Plasma and BMP13 on Rotator Cuff Tendon Injury Healing in a Rat Model. (December 2014) - Lamplot, Joseph D.; Angeline, Michael; Angeles, Jovito; Beederman, Maureen; Wagner, Eric; Rastegar, Farbod; Scott, Bryan; Skjong, Christian; Mass, Daniel; Kang, Richard; Ho, Sherwin; Shi, Lewis L.
Background: Although platelet-rich plasma (PRP) is used clinically to augment tendon healing, bone morphogenetic protein–13 (BMP13) may provide a better therapeutic avenue to improve early tendon healing and repair. Hypothesis: Exogenous expression of BMP13 in tenocytes will up-regulate genes involved in tendon healing. Direct delivery of adenovirus-mediated BMP13 (AdBMP13) into the injured rat supraspinatus tendon will increase biomechanical properties. Study Design: Controlled laboratory study. Methods: Exogenous expression of BMP13 and the major growth factors in PRP (transforming growth factor–β1 [TGF-β1], vascular endothelial growth factor–A [VEGF-A], and platelet-derived growth factor–BB [PDGF-BB]) was accomplished by using recombinant adenoviral vectors. The expression of tendon- and matrix-associated genes in growth factor–treated tenocytes was analyzed by use of semiquantitative reverse-transcription polymerase chain reaction. A total of 32 rats with supraspinatus defect were divided into 4 groups and injected with adenovirus-containing green fluorescent protein (AdGFP; negative control), PRP, AdBMP13, or PRP+AdBMP13. All rats were sacrificed at 2 weeks after surgery, and tendons were harvested for biomechanical testing and histologic analysis. Results: BMP13 up-regulated type III collagen expression compared with AdGFP control and PRP growth factors ( P < .01). BMP13 and PRP growth factors each up-regulated fibronectin expression ( P < .01). There was an increase in stress to failure in each of the 3 treatment groups ( P < .05 for PRP; P < .01 for AdBMP13 or PRP+AdBMP13) compared with AdGFP control. AdBMP13 demonstrated higher stress to failure than did the PRPs ( P < .01). The addition of PRP did not increase the BMP13-enhanced stress to failure or stiffness. The biomechanical results were further supported by histologic analysis of the retrieved samples. Conclusion: Exogenous expression of BMP13 enhances tendon healing more effectively than PRP as assessed by tendon- and matrix-associated gene expression, biomechanical testing, and histologic analysis. Clinical Relevance: While PRP is used in the clinical setting, BMP13 may be explored as a superior biofactor to improve rotator cuff tendon healing and reduce the incidence of retears.